Changes in Diverse Sexual and Contraceptive Behaviors Across College. Issue 8 (13th October 2019) - Lefkowitz, Eva S.; Vasilenko, Sara A.; Wesche, Rose; Maggs, Jennifer L.
Abstract : Researchers have made repeated calls for a better understanding of normative sexuality development during adolescence and young adulthood. We examined how the occurrence of seven penetrative, nonpenetrative, and contraceptive behaviors changed longitudinally across seven waves, and how individual (gender) and contextual (romantic relationship status) factors related to these changes in a sample of college students ( N = 730, M age = 18.4 at Semester 1; 51% female; 26% Hispanic/Latino American, 22% Black/African American, 30% Asian American/Pacific Islander, 45% White/European American). Across college, reported kissing, touching, performing and receiving oral sex, and penetrative sex rates increased, and contraception use (any type) and condom use (in particular) rates decreased, demonstrating changes with age independent of young adults' romantic relationship experiences. Rates of all sexual behaviors were higher, and of contraception use lower, when students were in serious romantic relationships. Contraception use decreased more for men than for women, particularly in semesters men were not in serious relationships. Condom use decreased for men, and for women in semesters they were in serious relationships. Findings demonstrate normative trends in sexuality development, as well as suggesting the value of enhanced sexual health promotion programming, with a particular focus on contraceptive behaviors, across college.